Dynamic identification method for flow patterns of liquid-solid two-phase flow in horizontal pipelines - ZHUJUNLIANG Junliang; ZHAOZHIFENG; WANGSHUGANG; JIANG Shuang (Zhileng xuebao)
The natural phenomenon of liquid-solid two-phase flow is extremely common and closely related to various human production and life processes. Obtaining the flow pattern of liquid-solid two-phase flow in pipelines is crucial for correcting real-time flow rates and ensuring the safe operation of the entire system in order to avoid blockages. The article is based on the Dynamic Mode Decomposition (DMD) algorithm, combined with a series of preprocessing measures, to reconstruct the flow pattern of liquid-solid two-phase flow. An experimental platform is built to verify the results, and the reconstruction effect is evaluated using relative error. The research results indicate that although there is some differences between the reconstructed flow pattern obtained by the DMD based identification method for liquid-solid two-phase flow patterns and the true flow pattern, the differences is within an acceptable range and can objectively reflect the evolution process of liquid-solid two-phase flow patterns. Compared with experimental and numerical simulation methods, the identification method of liquid-solid two-phase flow patterns based on DMD has significant advantages in data processing, accuracy, efficiency, and applicability. And it is not limited to specific scenarios, without the need to provide inherent logic of data, and can simultaneously obtain modes with a single frequency and growth rate and construct reduced order dynamic models, saving computational resources.